Bankruptcy Prediction of E-Commerce Companies on IDX Using Altman Z-Score, Springate, and Zmijewski - Yuantomi Rohmat Udin; Dika Puspitaningrum (Lembaga Pengembangan Kinerja Dosen, 2025)
This study investigates the bankruptcy risk of e-commerce technology companies listed on the Indonesia Stock Exchange (IDX) over the 2022–2024 period. A quantitative approach was used, supported by a descriptive research design. The study relies on secondary data obtained from the companies’ published historical financial statements. Bankruptcy risk was evaluated using three prediction models, namely the Altman Z-Score, Springate, and Zmijewski models, to compare how each model assesses the financial condition of the companies under study. The sample consists of PT Bukalapak.com Tbk, PT GoTo Gojek Tokopedia Tbk, and PT Global Digital Niaga Tbk. The findings reveal differences in the bankruptcy classifications generated by the three models. PT Bukalapak.com Tbk is identified as being in a relatively safe position based on the Altman Z-Score and Zmijewski models, whereas the Springate model categorizes the company as being in the bankruptcy zone in 2023 and 2024. In the case of PT GoTo Gojek Tokopedia Tbk, most of the models indicate continued signs of financial distress. PT Global Digital Niaga Tbk also presents contrasting results, as the Altman Z-Score and Springate models place the company in the bankruptcy zone, while the Zmijewski model indicates a safe financial condition. The differences in these results demonstrate that each prediction model has a distinct sensitivity to financial indicators, particularly those related to capital structure, liquidity, leverage, operational efficiency, and profitability. The findings suggest that bankruptcy prediction models can help management, investors, and creditors assess a company’s financial health and going concern.